Η φυσιολογική διαταραχή του ιώδους μεταχρωματισμού σε καρπούς μεσπιλιάς - Ευσταθίου, Επιφάνειος (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
Nowadays, loquat cultivation is constantly expanding in due to the high nutritional value of its fruits (carotenoids, antioxidants, etc.) and because loquats ripe during spring; a period with deficit of fleshy fruit in the market. Therefore, the need to investigate and solve important problems such as diseases, insects and physiological disorders affecting the quantity and quality of the fruit is increasing. The physiological disorder of the purple spot on loquat fruit, has significant economic impact on both quantitative and qualitative aspects. Purple spot is a violet-brown spot that is limited to the epidermal tissue of the fruit and is characterized by an irregular shape that affects up to 30% of the exposed area of the fruit. The disorder starts from the deeper layers of the skin and extends outward and not towards the flesh. However, a relatively small number of researchers have dealt with this disorder. The aim of the current study was to describe and justify the disorder, focusing on the most important findings of the literature. Additionally, through an experimental approach, the evolution of purple spot disorder was recorded in three cultivars (‘Obusa’, ‘Karantoki’, ‘Morphitiki’) with different intensity of symptoms. Phenotypic data of the progress of the disorder were recorded. The onset of the disorder has been attributed to the change in water relations between flesh and skin, during the color change stage of the fruit. In this stage completed the maximum concentration of sugars (90%) is reached in the flesh. Thus, with respect to abiotic factors (low temperatures and exposure to solar radiation) as well as cultivation practices such as thinning, flesh leads to better assimilation and sealing of sugars - minerals than to the skin. As a result, increasing the slope of the soluble substance concentration between the two tissues and causing dehydration in the skin responsible for the disorder. In the experimental part of the dissertation, the recording and evaluation of the fruits was carried out on a weekly basis, which lasted 8 weeks from the dilution stage until the fruits of the harvest matured. On January 17/2016, ten representative fruits were selected per variety, where they were marked with a numbered adhesive tape. Every week were taken photos on the selected fruits of each variety, and in order to have more complete details measured the length, width and color of each fruit. The results of the experimental process confirm all the factors responsible for causing the disorder, but they find the different sensitivity to the disorder between the three varieties. The most sensitive variety of the three studied were “Obusa”, then “Karantoki” and finally “Morphitiki”, which can be described as asymptomatic. For the further confirmation of the solubility imbalance between healthy and symptomatic tissue, the above finding of susceptibility of the varieties is proved after soluble solids analysis. (between varieties and the same fruit of the most susceptible variety). The ultimate aim of the dissertation is to create a background that will provide a basis for further research with molecular methods, determining if there are endogenous (genetic) factors that contribute to the disorder in cultivated varieties in Cyprus. Therefore, full justification and clarification of the disorder will be possible to solve the losses which is causes.
Keywords: Cultivation; Diseases; Fruit; Kαλλιέργεια; Mεσπιλιά; Aσθένειες